Dynamic Analysis of Correlation between Stock Market returns: An Empirical Study on Hong Kong and UK Stock Markets - Fan, Liyu (2012)
Abstract This paper examines the stock market correlation between Hong Kong and UK from January 3, 1990 to June 29, 2012, by using dynamic conditional correlation (DCC) analysis by Engle (2002). With the estimation of the time varying correlation from the Asymmetric dynamic Correlation Model, a regression model has been used to test whether the volatilities of individual markets induces changes in correlation. Additionally, two financial crises: 1997 Asian Financial Crisis and European Debt Crisis in latest years are also investigated as affecting factors on correlation in the regression model. The result suggest that the correlation between the returns of Hong Kong’s stock market index and UK’s stock market index, fluctuates over time and the changes in correlation is significantly influenced by the individual volatility of the market index return. Specifically, the correlation increases when the market volatilities become high. This may infer a reducing opportunity to make a beneficial international diversification over these two stock markets. In addition, occurrences of the two financial crises have different impacts on correlation during the crisis period.